Efektivitas Aplikasi JSS Sebagai Implementasi E-Government Kota Yogyakarta - Nabila Nur’aini; Muhamad Faisal Abdul Latif; Naufal Falah Ardiansyah (UIN Sunan Gunung Djati Bandung, 2024)
The rapid development of technology in recent years has led to several changes in various lines of life. One of them has an impact on the government sector, several new policies are now present along with the development of technology. The use of technology in the government bureaucracy can improve city management functions. The presence of e- government is one of the steps of utilizing technology in the government bureaucracy, especially in the field of public services. One of the cities in Indonesia that i mplements e- government is Yogyakarta City, Yogyakarta City Government has a public service application, namely the Jogja Smart Service Application. The purpose of this research is to determine the effectiveness of the JSS application in the implementation of e-government in Yogyakarta City. This research was conducted using mixed methods. Mixed method is a combined method between qualitative methods as well as quantitative methods. Qualitative method data collection techniques use literature studies while quantitative methods use descriptive methods. The population of this study was 5000 people of Yogyakarta City who used the JSS Application. The sample in the study was 1200 people of Yogyakarta City who used the JSS Application. It can be concluded that the Jogja Smart Service (JSS) application is not yet fully effective. This JSS application already has a target achievement of orderly population administration to make it a city hall in cyberspace. However, this application is not yet adaptive because of the many problems that occur in this application.